2019
DOI: 10.13170/depik.8.2.12155
|View full text |Cite
|
Sign up to set email alerts
|

Sintasan dan pertumbuhan cacing Polychaeta Nereis sp. dari kawasan pertambakan Desa Jeruklegi Cilacap dengan salinitas media pemeliharaan dan jenis pakan berbeda

Abstract: Polychaeta Nereis sp. is one of the natural foods that can trigger the maturation of shrimp gamete cells up to 70%, but the fulfillment of Nereis sp. still rely on the arrest from nature. This condition encourages the cultivation of Nereis sp., but knowledge of the biological aspects of Nereis sp. still very lacking, so it needs further research. This study aims to determine the survival and growth of Nereis sp. from Cilacap Jeruklegi area with different salinity and feed as basic information for the cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The increase in the number of segments and the body weight -both variables had a strong positive correlation (Figure 3) -indicates the animals' growth, and can be affected by several factors such as salinity and feed. A research by Wibowo et al (2019) suggested that the polychaete worms Nereis sp. fed by animal protein had a greater number of segments and weight compared to the worms fed by vegetable protein.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the number of segments and the body weight -both variables had a strong positive correlation (Figure 3) -indicates the animals' growth, and can be affected by several factors such as salinity and feed. A research by Wibowo et al (2019) suggested that the polychaete worms Nereis sp. fed by animal protein had a greater number of segments and weight compared to the worms fed by vegetable protein.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa pada salinitas 15 ppt menghasilkan retensi protein yang sama saat diberi pakan berprotein hewani maupun protein nabati, hasil ini menunjukkan bahwa salinitas 15 ppt merupakan salinitas optimum untuk pemeliharaan Nereis sp. hasil ini sesuai dengan penelitian Wibowo et al (2019a) Selama pemeliharaan 2 bulan dengan perlakuan salinitas 5, 15, dan 25 ppt dan pemberian pakan berprotein hewani maupun nabati belum menunjukkan perbedaan dalam perkembangan gonadnya dibandingkan dengan awal perlakuan. Hasil ini menunjukkan Nereis sp.…”
Section: Pembahasanunclassified
“…Based on data in 2012 from the Directorate of Aquaculture, the need for frozen Polychaeta imports continues to increase due to undeveloped marine worm cultivation in Indonesia, seen from the total import value of 2,550 tons with a value of US $ 17,973.80 it can be said to be very potential, to be developed in the future (Anonymous, 2012 in Rasidi, 2013). According to Wibowo et al (2019), Nereis sp. Very good for use as broodstock feed for shrimp because there is a high nutrient content and protein source that can improve the quality of gamete cells and the viability of shrimp larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has not done much research on marine worms, especially in terms of density in the cultivation of Nereis sp. Some examples of research that have been successfully carried out by Asnawi et al (2018) used a density of 5 individuals / container with a diameter of 50 cm, while research conducted by Wibowo et al (2019) used a density of 10 individuals / container area of 0.06 m 2 or about 167 individuals / m 2 . Therefore, it is important to do research on stocking density because it is closely related to the production and growth rate of cultivated biota, so this research aims to determine the most effective stocking density for survival and increase the biomass of Nereis sp.…”
Section: Introductionmentioning
confidence: 99%